The Relationship Between Shoulder Arm Muscle Power and the Ability to Punch the Court Tennis Drive in Students of the 2022 FKIP USK Physical Education Study Program - Syamsulrizal Syamsulrizal; Masyita Siregar; Muhammad Iqbal; Liasar Liasar; Arfi. R; Fajar Fajar; Yunadi Yunadi (Departement of Mathematics Education, 2024)
Field observations obtained when I was on the committee of the Field Tennis League (LITEL) from these players stated that to achieve high tennis achievements, supported by good physical, technical, tactical and mental conditions, especially when hitting drives on sportsmen is a requirement that cannot be neglected, especially the game of court tennis. This type of research can be classified under Descriptive research as stated by Arikunto (1991: 63) that